Kepuasan Pasien Rawat Jalan terhadap Pelayanan Kefarmasian di Rumah Sakit dan Puskesmas di 11 Provinsi di Indonesia - Prihartini, Nita; Yuniar, Yuyun; Susyanty, Andi Leny; Raharni, Raharni (Jurnal Kefarmasian Indonesia, 2020)
Pharmaceutical services is a direct service and responsible to patients relating to pharmaceutical products aimed to improve the quality of life of patients. Quality of pharmaceutical services can be assessed based on outpatient satisfaction. The aim of the study was to compare the satisfaction of outpatients with pharmaceutical services in hospitals and primary health care. This study used a cross-sectional comparative study design and was conducted in February-November 2017 in 11 provinces, each province consisting of 2 districts/cities selected purposively. Samples were outpatients who got medicines in hospitals or primary health care at least 31 patients in each pharmacy. Satisfaction was assessed by the dimension of responsiveness, reliability, collateral, friendliness, and physical evidence. Data was collected by the questionnaires and analyzed using chi-square test. The results of the study show that outpatient satisfaction with pharmaceutical services in hospital and primary health care was 90,9% and 96.6%, respectively. The largest percentage of outpatients in hospitals and primary health care are in the age group of 40-59 years, female, has further education, and not working/housewives. There were significant differences in the age group, gender, and education of outpatients between hospitals and primary health care. There was no significant relationship between the characteristics (age, sex, education, occupation) of outpatients and satisfaction with pharmaceutical services in hospitals and primary health care